The Contradictions of Market Socialism (Policy Press, 2026)
Available open access digitally under CC-BY-NC-ND licence. China and Vietnam are two of the remaining constitutionally socialist countries that are single-handedly governed by Communist parties. Their rapid economic growth has gone hand in hand with the deepening commodification of labour and the restructuring of welfare – producing new tensions between workers’ needs and state priorities. Grounded in rich empirical research from diverse regions of both countries, this book explores how everyday struggles for livelihoods and wellbeing are shaped by increasingly flexible labour regimes and welfare systems offering minimal protection. It reveals how such systems encourage self-entrepreneurship and individual responsibility, while exposing the conflict between ensuring workers’ wellbeing and maintaining the market socialist model. Connecting labour and welfare transformations to broader political-economic processes – including land restructuring and financialisation – the book offers an unparalleled comparative perspective on two of the world’s most important manufacturing hubs.